Possibilities of safe yield increase in the Wydrzany well field (Uznam Island, Poland) by surface water from a drainage system - Hoc, Ryszard; Sadurski, Andrzej; Wiśniowski, Zenon (Geologos, 2019)
In parallel with intensified development of the Polish part of Uznam Island, there is an increase in the demand for drinking water in this area. This island ranks among areas with low water resources, which at the present time are allocated. In order to create the prospect of increased groundwater resources, a concept has been developed that allows for the recovery of part of the freshwater from drainage systems which discharge into the waters of Szczecin Lagoon or the River Świna. The present article discusses the secondary use of water from drainage systems for supply of the Wydrzany resource area. The notion of using water from the White Bridge pumping station was considered the most promising. The catchment area of the polder is 880 ha, 280 ha of which are located on Polish territory. The White Bridge pumping station transfers water from the polder, which it leads to the Peat Channel which, in turn, drains water gravitationally into Szczecin Lagoon. Here, results of simulations aimed at the use of drainage water to improve upon groundwater resources in the “Wydrzany” intake are discussed. On the basis of these simulations of artificial water supply to the intake, an increase of available resources by up to 50 per cent may be expected.